Analysis of Handling Performance Installation on Vehicle due to Vehicle Rear Subframe - Jamal, Usman; Sulaiman, Syabillah; Azizul, Muhamad Asri (Progress in Engineering Application and Technology, 2023)
Handling capabilities are essential for a vehicle's dynamic properties, but objective evaluation methods lack consistency with subjective assessment, while subframes isolate vibrations, distribute loads, and support the body structure, and excessive subframe vibration can lead to oversteer and loss of control, emphasizing the importance of efficiently absorbing vibration impacts for customer satisfaction and driving comfort. The objective of this experimental study is to analyze the vibration of the rear subframe during handling motions, develop a data acquisition system for capturing vehicle dynamic motion, while the scope includes conducting the experiment on a Perodua Myvi 1300cc at UTHM Pagoh campus. The experimental study utilized subframe bar, Arduino Uno, accelerometer, Arduino IDE, and MATLAB Simulink to measure the lateral acceleration of the vehicle conducted within the speed limit of the institution. The absence of a subframe bar in a vehicle leads to increased acceleration, slightly higher dynamic behavior and requiring precise steering control to maintain stability safely. The study aimed to examine subframe vibration during handling motions, particularly the impact of a subframe bar, through tight double-lane change maneuvers at 10 km/h, the left subframe mount shows a difference of 0.08 g and 0.03 g between subframe bar and no subframe bar conditions, while the right subframe mount shows a difference of 0.28 g and -0.41 g. At 20 km/h, the left subframe mount shows a difference of 0.15 g and 0.34 g, while the right subframe mount shows a difference of 0.19 g and -0.38 g. At 30 km/h, the left subframe mount shows a difference of approximately 0.22 g and -0.29 g, while the right subframe mount shows a difference of 0.39 g and -0.09 g. This study provides valuable insights into subframe behavior, vehicle dynamics, and the importance of the subframe bar in enhancing rigidity and stability, with recommendations for improving research accuracy and reliability.